Tolerance of Religious People in Nusa Jaya Villages, District III of Belitang, South East Regency, South Sumatera Province at 1961-2013 - Agus Susilo (Yupa: Historical Studies Journal, 2017)
This research described how life tolerance of religion in Nusa Jaya Village Belitang District III Regency OKU East Sumatera Selatan, besides to know the factors that cause success tolerance of religion in Nusa Jaya Village Belitang District III Regency of OKU East of South Sumatera. Tolerance is a problem that often arises throughout the time, especially tolerance among religious people. Historically, the religious nature of tolerance does not just appear. This research aims to determine the factors that lead to the success of religious, between Islam, Catholicism, Protestant Christianity, and Buddhism in the Nusa Jaya village, District III of East Belitang, District of OKU, South Sumatra. The method used in this study is the historical method, obtained through in-depth interviews, documentation and literature study. The results showed that normatively the basic values that form the basis of the establishment of tolerance among religious people is the value of religion and cultural Javanese descendants. While empirically composed of human values, nationalism, historical, exemplary public religious leaders and the value of patience.